Rock, Rádio FM e Rio de Janeiro : uma análise das estratégias de incursão da Fluminense "A Maldita" e da Cidade "A Rádio Rock" no domínio das guitarras - Silva, Heitor da Luz (2010)
This dissertation aims to analyze the media strategies of two radio stations that acted as rock radio in Rio de Janeiro in two distinct moments: Fluminense FM station, in the beginning of the eighties, and Cidade Station, in the the first years of 2000 years. The research has as a main reference the idea of musical genre (FABBRI, 1981; FRITH, 1997; JANOTTI JR, 2003) articulated to the notion of taste community (FRITH, 1997), highlighting also the existence and the importance of symbolic capitals specific to mass popular music (JANOTTI JR, 2007; THORNTHON, 1997). We work with the hypothesis that, for the better part, thanks to the fact of that they adopt different strategies to establish themselves, symbolically, as rock stations for the audience and the other local social agents interested in the genre (affectively or market-wise, or in the both ways), that one of them (the Fluminense) tends to have a bigger social recognizing than the other one (the Cidade) in your context of acting. As a consequence of this first hypothesis, we work with a second, no less important: that there is a relation between the kind of symbolic configuration of each station, thanks to their strategies, and the roles the both of them played in the local musical market. Thanks to the way that each one relates to the cultural mediation enforced by the notion of genre, Fluminense Maldita and Cidade Rock presented distinct levels of autonomy in relation to the other market agents. Fluminense FM served to more agents that tried to be part of this market because of the higher level of autonomy that it obtained in relation to them, especially the big record companies and the influence of their economic power. So, this station helped, in a more effective way, to move the musical market in its context, allowing new actors to have some media visibility.